OPTIMALISASI KINERJA KARYAWAN MENGGUNAKAN ANALISIS PENUGASAN - Rizal Umar Nugroho; Rikjan Rohmatul Malik; Rofi Muhammad Ardiansyah; Somadi Somadi (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2026)
Optimizing employee allocation is a crucial element in increasing the productivity of the manufacturing industry, especially in the garment production process. In an effort to compile optimal assignments at CV.Russ&Co Bandung, the Hungarian method is used. The Hungarian method is a method for determining resource allocation to a particular task one by one. Assignment of 4 employees to 4 work stations (cutting, screen printing, sewing, packing) at CV. Russ&Co Bandung demonstrated significant inefficiencies with a total initial production time of 1,970 minutes. The research approach used is a descriptive quantitative approach with data collection through observation and interviews regarding performance data and employee assignments in several CV operational divisions. Russ&Co Bandung. This research aims to determine optimal assignments based on an individual working time matrix using the Hungarian Method. Data collection was carried out through direct observation during 5 effective working days (Monday-Friday) during peak production periods to capture variations in daily workload. The selection of this period ensures a representation of the company's real operational conditions. The Hungarian method was applied manually and verified with POM-QM for Windows software for computational validation. The results of the analysis produced optimal allocations of Wibowo-cutting (165 minutes), Rizal-screen printing (90 minutes), Kevin-tailoring (95 minutes), Fikri-packing (85 minutes) with a total time of 435 minutes, achieving a reduction of 1,535 minutes or 78% efficiency. This improvement proves the effectiveness of the Hungarian method in solving small-medium scale assignment problems in local manufacturing.